Testing the Environmental Kuznets Curve Hypothesis in Uruguay using Ecological Footprint as a Measure of Environmental Degradation - Ergun, Selim Jürgen; Rivas, Maria Fernanda (International Journal of Energy Economics and Policy, 2020)
This paper, using data for the time period 1971-2014, analyzes the relationship between GDP per capita, foreign direct investment, energy use per capita, and environmental degradation measured by the Ecological Footprint in Uruguay. It also tests whether the Environmental Kuznets Curve (EKC) hypothesis holds. While environmental degradation is positively related with energy use per capita in the long run, its relationship with foreign direct investment in the long-run is negative. The inverted U-shaped relationship between GDP per capita and environmental degradation implies that the EKC hypothesis is verified. The policy recommendations include the implementation of measures leading to more energy saving and more efficient use of energy, investing in cleaner and more efficient technologies, and policies that would increment the share of modern renewable sources in energy consumption. Keywords: Environmental Kuznets Curve, Ecological Footprint, Gross Domestic Product per Capita, Energy Use, Foreign Direct Investment, Uruguay JEL Classifications: Q4, Q53 DOI: https://doi.org/10.32479/ijeep.9361